Penicillin dried blood spot assay for use in patients receiving intramuscular benzathine penicillin G and other penicillin preparations to prevent rheumatic fever - Page-Sharp, Madhu; Coward, J.; Moore, Brioni; Salman, S.; Marshall, L.; Davis, T.; Batty, Kevin; Manning, L. (American Society for Microbiology, 2017)
© 2017 American Society for Microbiology. All Rights Reserved. Rheumatic heart disease (RHD) remains an important global health challenge. Administration of benzathine penicillin (BPG) every 3 to 4 weeks is recommended as a secondary prophylaxis to prevent recurrent episodes of acute rheumatic fever and subsequent RHD. Following intramuscular injection, BPG is hydrolyzed to penicillin G (benzylpenicillin). However, little is known of the pharmacokinetics (PK) of BPG in pediatric populations at high risk of RHD or of the pharmacokinetic-pharmacodynamic relationship between penicillin exposure and clinically relevant outcomes. Dried blood spot (DBS) assays can facilitate PK studies in situations where frequent venous blood sampling is logistically difficult. A liquid chromatography-mass spectroscopy assay for penicillin G in plasma and DBS was developed and validated. Application of the DBS assay for PK studies was confirmed using samples from adult patients receiving penicillin as part of an infection management plan. The limit of quantification for penicillin G in DBS was 0.005 mg/liter. Penicillin G is stable in DBS for approximately 12 h at room temperature (22°C), 6 days at 4°C, and 1 month at 20°C . Plasma and DBS penicillin G concentrations for patients receiving BPG and penicillin G given via bolus doses correlated well and had comparable time-concentration profiles. There was poor correlation for patients receiving penicillin via continuous infusions, perhaps as a result of the presence of residual penicillin in the peripherally inserted central catheter, from which the plasma samples were collected. The present DBS penicillin G assay can be used as a surrogate for plasma concentrations to provide valid PK data for studies of BPG and other penicillin preparations developed to prevent rheumatic fever and RHD.